Pemanfaatan Metode Reading Aloud Terhadap Motivasi Belajar PAI Siswa di Sekolah Dasar - Yola Lestari; Rahmi Wiza (Prodi Pendidikan Keagamaan Islam, 2023)
This study aims to determine the use of the reading aloud method on student learning motivation in PAI subjects at SDN 34 Beringin Singgalang. This study uses a qualitative method with a descriptive approach. This research was conducted at SDN 34 Beringin Singgalang. Data collection techniques used are observation, documentation and interviews. The results of this study indicate that: (1) The process of implementing the reading aloud method at SDN 34 Beringin Singgalang takes 3 forms, namely planning, implementation and evaluation. (2) There are 2 forms of students' learning motivation using the reading aloud method, namely intrinsic motivation in the form of challenge, curiosity, self-control, and fantasy. While extrinsic motivation in the form of parental sanctions, gifts, punishments, and praise. (3) Constraints in the use of the reading aloud method, namely the limited facilities and infrastructure, the condition of the classrooms that are next to other classes, students feel bored with reading that is monotonous, and the management and supervision of the class is lacking.